2011
DOI: 10.1007/s12600-011-0154-8
|View full text |Cite
|
Sign up to set email alerts
|

Diofenolan: a novel insect growth regulator in common citrus butterfly, Papilio demoleus

Abstract: Penultimate and last instar larvae of the common citrus swallowtail butterfly, Papilio demoleus L. (Papilionidae: Lepidoptera), were treated with different doses of a novel juvenoid, diofenolan. Several deformities were observed as a result of topical administration of diofenolan which include delay in larval-larval and larval-pupal ecdysis, ecdysial failure, mortality, severe reduction in pupation, deformed pupae and complete inhibition of adult emergence. The juvenoid diofenolan severely hampers the normal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
5
15
0
Order By: Relevance
“…Also, larval duration was generally prolonged and the developmental rate of these larvae was regressed, in almost dose-dependent manner. This inhibited growth of P. unionalis by methoxyfenozide was in accordance with those reported results of inhibited growth of some insects by various IGRs, such as S. littoralis by flufenoxuron (Bakr et al, 2010), lufenuron (Adel, 2012), and novaluron (Ghoneim et al, 2015); P. demoleus by Diofenolan (Singh and Kumar, 2011), S. litura by chlorfluazuron (Perveen, 2012), Aedes aegypti (Farnesi et al, 2012), Culex pipiens by novaluron (Djeghader et al, 2014) and kinoprene (Hamaidia and Soltani, 2014). Likewise, some IGRs failed to affect the growth of different insects, such as M. domestica (Ghoneim et al, 1991), Periplaneta americana and Oncopeltus fasciatus (Darvas et al, 1992), Spodoptera exempta, Spodoptera exigua, and Leptinotarsa decemlineata (Smagghe and Degheele, 1994).…”
Section: Inhibited Growth and Retarded Development Of P Unionalis Bysupporting
confidence: 90%
See 2 more Smart Citations
“…Also, larval duration was generally prolonged and the developmental rate of these larvae was regressed, in almost dose-dependent manner. This inhibited growth of P. unionalis by methoxyfenozide was in accordance with those reported results of inhibited growth of some insects by various IGRs, such as S. littoralis by flufenoxuron (Bakr et al, 2010), lufenuron (Adel, 2012), and novaluron (Ghoneim et al, 2015); P. demoleus by Diofenolan (Singh and Kumar, 2011), S. litura by chlorfluazuron (Perveen, 2012), Aedes aegypti (Farnesi et al, 2012), Culex pipiens by novaluron (Djeghader et al, 2014) and kinoprene (Hamaidia and Soltani, 2014). Likewise, some IGRs failed to affect the growth of different insects, such as M. domestica (Ghoneim et al, 1991), Periplaneta americana and Oncopeltus fasciatus (Darvas et al, 1992), Spodoptera exempta, Spodoptera exigua, and Leptinotarsa decemlineata (Smagghe and Degheele, 1994).…”
Section: Inhibited Growth and Retarded Development Of P Unionalis Bysupporting
confidence: 90%
“…2). (Bakr et al, 2013), buprofezin (Nasr et al, 2010), methoxyfenozide (Pineda et al, 2004) and cyromazine (Tanani et al, 2015) against Spodoptera littoralis; pyriproxyfen against Eurygaster integriceps (Mojaver and Bandani, 2010); diofenolan against Papilio demoleus (Singh and Kumar, 2011); diflubenzuron against Halyomorpha halys (Kamminga et al, 2012); chlorfluazuron against Spodoptera litura (Perveen, 2012); flufenoxuron and pyriproxyfen against Locusta migratoria (Hu et al, 2012); kinoprene against Culex pipiens (Hamaidia and Soltani, 2014); flufenoxuron and methoprene against Agrotis ipsilon (Khatter, 2014) and lufenuron against Tribolium castaneum (Gado et al, 2015). Recently, IGRs exhibited various toxicities against some insects, such as pyriproxyfen against Spodoptera mauritia (Resmitha and Meethal, 2016); lufenuron and methoxyfenozide against T. castaneum (Ali et al, 2016); methoxyfenozide against C. pipiens (Hamaidia and Soltani, 2016); tebufenozide against Ephestia kuehniella (Tazir et al, 2016); lufenuron against Glyphodes pyloalis (Aliabadi et al, 2016) and Helicoverpa armigera (Vivan et al, 2016); fenoxycarb against Corcyra cephalonica (Begum and Qamar, 2016); methoprene and pyriproxyfen against Culex quinquefasciatus and Aedes albopictus (Khan et al, 2016); cyromazine against Musca domestica, Stomoxys calcitrans and Fannia canicularis (Donahue et al, 2017); novaluron against Pectinophora gossypiella (Ghoneim et al, 2017a) and P. unionalis (Ghoneim et al, 2017b).…”
Section: Effects Of Methoxyfenozide On Growth Development and Metamomentioning
confidence: 99%
See 1 more Smart Citation
“…This inhibitory effect on the larval-pupal development due to high JH titre has been attributed to an inhibitory effect on PTTH which in turn has an indirect inhibitory effect on the secretion of ecdysteroids (Nijhout 1998). The formation of larval-pupal-adult chimeras resulting from treatment with root extracts of W. somnifera has also been observed in treatment with JHA, diofenolan Unauthenticated Download Date | 5/11/18 1:45 AM (Singh and Kumar 2011a). It has been suggested that plant extracts are juvenile hormone mimics (Munoz et al 2013) and are capable of arresting the larvalpupal or pupal-adult transformation (Sahayaraj and Sathyamoorthi 2010).…”
Section: Discussionmentioning
confidence: 96%
“…The insects suffering from ecdysial stasis were unable to cast off old larval cuticle that was found all over the body resulting into complete ecdysial stasis or remained attached to different parts of the pupal body showing partial ecdysial stasis. These effects have also been observed as a result of administration of IGRs (lufenuron and diflubenzuron) to fifth instar larvae of H. armigera (Butter, Singh, & Dhawan, 2003;Unsal, Ozparlak, & Aktumsek, 2004) and JHAs (diofenolan and pyriproxyfen) to last instar larvae of Papilio demoleus (Lepidoptera: Papilionidae) and S. litura (Singh & Kumar, 2011a, 2011b, 2015a. In the last larval stadium of holometabolous insects, the JH titer is high during the initial phase of final stadium but subsequently it declines to undetectable levels.…”
Section: Discussionmentioning
confidence: 85%